The Effect of Good Corporate Governance on Financial Performance of The Company (Empirical Study on Manufacturing Company of Consumer Goods Sector Industry Listed On Indonesia Stock Exchange Year 2015- 2016) - Anita Wijayanti, Agusti Sekar Putri Prabowo, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to examine the influence of the implementation of good corporategovernance to the financial performance of the company. Good corporate governance isan independent variable that is measured using the following components: number ofboards of directors, the proportion of board of commissioners, company size, and Debtto Equity Ratio. While the companys financial performance is a dependent variablemeasured by Return On Equity (ROE). The population in this research is allmanufacturing companies of consumer goods industry sector listed in Indonesia StockExchange and continuously publish the financial report in 2015 until 2016. Pursuant topurposive sampling method, the sample obtained counted 34 company every year inyear period 2015-2016, so the data obtained as much as 68 data observation. The resultof this research shows that the proportion of board of commissioner has positiveinfluence to company performance, and while the number of a board of directors, firmsize and Debt to Equity Ratio there is no significant effect to financial performance.Based on the determination coefficient test (R2) obtained the coefficient ofdetermination with value R2 obtained is 0.277 and when converted to percent to 27.70%.This result shows the percentage of contribution of board of director, proportion ofboard of commissioner, firm size and debt to equity ratio to company financialperformance equal to 27,70% while the rest equal to 72,30% influenced by othervariables not included in this research model.Keywords: Good Corporate Governance, Corporate Financial Performance.